DEVELOPMENT APPLICATION 'CALISTUNG' AS MEDIA LEARNING GAMES EDUCATION BASED ANDROID FOR CHILD AGE EARLY - ina rosmalita (Jurnal Scientia, 2022)
Development of an Android-Based Educational Game to Improve Reading, Writing and Counting Skills for 5-6 Year Old Children at the Cahaya Bunda Kindergarten at IT Cahaya Bunda Ketapang. This study aims to produce an Android-based educational game for early childhood. This study uses the Research and Development method with the ADDIE development model. Data collection techniques using a questionnaire. The results of the validation of the development of android-based educational games are suitable for use with the average result of Aiken's V by material experts, which is 3.84 and with the average result of Aiken's V by media experts, which is 3.88. The practical results of android-based educational games are said to be very practical with an average percentage result of 3.83, which is very practical with the educational game Calistung, the android application is very feasible to use. It can be concluded that android-based educational games to improve the reading skills of children aged 5-6 years in Ketapang are valid, practical, and effective.